Quercetin Prevents Escherichia coli O157:H7 Adhesion to Epithelial Cells via Suppressing Focal Adhesions - Xue, Yansong; Du, Min; Zhu, Mei-Jun (Frontiers in Microbiology, 2019)
The attachment of E. coli O157:H7 to host intestinal epithelial cells is indispensable for its pathogenesis. Besides translocated-intimin receptor (Tir), E. coli O157:H7 can interact with host cell surface receptors to promote intimate adhesion. In this study, we found that integrin β1 was increased in Caco-2 cells upon infection. Caco-2 cells subjected to integrin β1 antibody blocking or CRISPR/Cas9 knockout had reduced bacterial attachment. Infection of E. coli O157:H7 resulted in inactivated focal adhesion kinase (FAK) and paxillin, increased focal adhesion (FA) and actin polymerization, and decreased host cell migration, which were rescued by integrin β1 antibody blocking or knockout. Immunoprecipitation analysis further showed an interaction between bacterial intimin and integrin β1, while intimin deletion mutant (Δeae) strain was unable to cause FAK and paxillin dephosphorylation and FA accumulation. Pre-treatment with quercetin, known for its anti-oxidant and anti-inflammation functions, reduced bacterial infection to host cells, which might be partially attributed to the prevention of integrin β1 and FAK association augmented by E. coli O157:H7. In addition, quercetin decreased FA formation induced by bacterial infection and recovered host cell motility. Taken together, our results showed that E. coli O157:H7 interacts with integrin β1 to attach to host cells. This interaction inhibits FAK, increases FA formation and decreases cell mobility, which facilitates bacterial attachment. Quercetin prevents excessive integrin β1 expression induced by E. coli O157:H7 and inhibits bacterial infection. Besides, quercetin reduces FA assembly and possibly blocks the interaction between integrin β1 and FAK. Thus, quercetin might be an alternative antimicrobial compound to reduce bacterial attachment and infection in the host.